Dayak Ngaju Customary Law's Criminal Sanctions Agains Adultery in Palangka Raya - Wardhani, Novea Elysa; Kirstanto, Kiki; Januardy, Ivans; Putri, Anggelia Widya (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2024)
The law in each society has its own style and nature. Customary law is a law that always grows from a real need for life and a way of life in society, which is the whole culture of the community where customary law applies. Customary law if violated will certainly be subject to sanctions. Customary law in Palangka Raya against perpetrators of adultery will be punished in the form of sanctions, namely by paying a singer or jipen fine to complete peace according to Dayak Ngaju custom. Based on the facts in the field, if a criminal act of adultery is committed by a wife with an unmarried man against her husband, it certainly raises questions about Damang's authority as Dayak Traditional Chairman so that it can be known and understood that what are the legal acts in the settlement of adultery committed by the perpetrator.